2021
DOI: 10.3389/fphar.2021.732345
|View full text |Cite
|
Sign up to set email alerts
|

Opioids and Gabapentinoids Utilisation and Their Related-Mortality Trends in the United Kingdom Primary Care Setting, 2010–2019: A Cross-National, Population-Based Comparison Study

Abstract: Background: There is growing concern over the increasing utilisation trends of opioids and gabapentinoids across but there is lack of data assessing and comparing the utilisation trends across the four United Kingdom countries. We assessed/compared opioids and gabapentinoids utilisation trends across the four United Kingdom countries then evaluated the correlation between their utilisation with related mortality.Methods: This repeated cross-national study used Prescription Cost Analysis (PCA) datasets (2010–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“… 1 In many countries, the prescribing and overall consumption of gabapentinoids has increased sharply. 2 , 3 A significant part of this trend is attributed to the common off-label use of gabapentinoids and the ongoing efforts of clinicians not to rely on opioids in the treatment of various pain conditions. 4 In Serbia, gabapentinoids are approved for the treatment of neuropathic pain and as adjunctive therapy for focal seizures in patients with epilepsy, while pregabalin has an additional indication for the treatment of generalized anxiety disorder.…”
Section: Introductionmentioning
confidence: 99%
“… 1 In many countries, the prescribing and overall consumption of gabapentinoids has increased sharply. 2 , 3 A significant part of this trend is attributed to the common off-label use of gabapentinoids and the ongoing efforts of clinicians not to rely on opioids in the treatment of various pain conditions. 4 In Serbia, gabapentinoids are approved for the treatment of neuropathic pain and as adjunctive therapy for focal seizures in patients with epilepsy, while pregabalin has an additional indication for the treatment of generalized anxiety disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, non-pharmacological treatments, such as group exercise programmes or psychological therapy, should be offered first to help manage pain [ 1 ]. Opioids are associated with central nervous system depression, dependence, and possibly an increase in all-cause mortality [ 10 , 11 , 12 ]. In the UK, the Medications and Healthcare products Regulatory Agency now recommend that overdose risk should be communicated to all patients prescribed opioids for chronic pain [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coffin et al also identified that reduced access to prescribed opioids amongst patients previously reliant on their prescription was related to an increased use of non-prescription opioid analgesia [ 17 ]. In the CNCP population, polypharmacy (the use of multiple medications at the same time, including the co-prescribing of other central nervous system depressants), high dose opioids (≥50 morphine milligram equivalent per day), histories of non-prescription substance use, and co-morbid mental and physical health conditions are all risk factors for opioid-related harms, including overdose [ 6 , 10 , 18 ]. Additionally, CNCP is over-represented in people who use non-prescription substances [ 19 , 20 ], and this has also been found in the Scottish context [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to inadequate pain relief, the use of opioids for pain management is challenged by significant adverse effects including physical dependence, tolerance, sedation, dizziness, constipation, nausea, vomiting, and respiratory depression ( 3 ). Trends in opioid prescription and the associated mortality continue to be problematic not only in the US, but also in other countries ( 4 , 5 ). Multimodal approaches for pain management such as combination therapy with both nonpharmacological means in addition to traditional pharmacological therapeutics can be effective in achieving optimal control of pain ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%